2022
DOI: 10.3390/ma15175900
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Strained Stanene Compared to That of Graphene

Abstract: Stanene, composed of tin atoms, is a member of 2D-Xenes, two-dimensional single element materials. The properties of the stanene can be changed and improved by applying deformation, and it is important to know the range of in-plane deformation that the stanene can withstand. Using the Tersoff interatomic potential for calculation of phonon frequencies, the range of stability of planar stanene under uniform in-plane deformation is analyzed and compared with the known data for graphene. Unlike atomically flat gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In our recent work [63], molecular dynamics simulations using the Tersoff potential showed that a free-standing stanene can transform into a planar configuration with h = 0 for a sufficiently large tensile strain in the plane. Unloading results in the return of the buckled structure, and there are two possible paths of buckling with the same energy, depending on which of the two triangular sublattices is shifted in the positive normal direction.…”
mentioning
confidence: 98%
“…In our recent work [63], molecular dynamics simulations using the Tersoff potential showed that a free-standing stanene can transform into a planar configuration with h = 0 for a sufficiently large tensile strain in the plane. Unloading results in the return of the buckled structure, and there are two possible paths of buckling with the same energy, depending on which of the two triangular sublattices is shifted in the positive normal direction.…”
mentioning
confidence: 98%